Studies on the livestock of southern Darfur, Sudan. III. Production traits in sheep - Wilson, R.T. (Springer, 1976)
The result of an intensive 15 months study of 10 flocks of indigenous sheep is recorded. Lambing rates approach 1.5 lambs per ewe per year, but a death rate of 23 percent and on off take of 27 per cent, means that flock numbers are probably slightly declining. Twins account for 14 per cent of all births but the death rate of twin lambs is almost twice that of single lambs up to 6 months of age. Increased productivity is therefore more likely to be achieved by improving the survival and growth rates of single lambs that by selection for twining. The weighed average rate of lightweight gain for all surviving lambs is 82g per day up to 1 year of age, and is better than that recorded for any other indigenous African sheep. Meat production per kg of breeding female, at 0.253 kg up to 6 months of age of the young, is almost six times the production of cattle under the same management and environmental conditions, but is inferior to that of goats.